in Vitro Maturation of Human Oocytes - Yu-Hung Lin; Jiann-Loung Hwang (Elsevier, 2006)
Immature oocyte retrieval followed by in vitro maturation (IVM) opens a new horizon for modern assisted reproductive technologies (ART). Recent studies in IVM make it a feasible alternative to in vitro fertilization. Antral follicle count is correlated with the pregnancy rate, so women with polycystic ovarian syndrome or polycystic ovaries are the best candidates for IVM. IVM can also be offered to women at risk of ovarian hyperstimulation syndrome or poor responders. From the available information, IVM is a safe procedure and does not increase congenital anomalies or pregnancy complications. Further research is necessary in order to apply this technique to other patients.